Memory in World War I American museum exhibits - Marsh, Hannah (Kansas State University, 2014)
As the world enters the centennial of World War I, interest in this war is reviving. Books, television shows, and movies are bringing the war into popular culture. Now that all the participants of the war have passed away a change is occurring in in American memory. The transition from living to non-living memory is clearly visible in museums, one of the main ways history is communicated to the public. Four museums are studied in this paper. Two exhibits built in the 1990s are in the 1st Infantry Division Museum at Fort Riley, Kansas, and the Chemical Corps Museum in Fort Leonard Wood, Missouri. The other two exhibits are newer and are the National World War I Museum in Kansas City, Missouri and the Cantigny 1st Infantry Division Museum in Wheaton, Illinois. Findings reveal that exhibits become more inclusive over time to civilian bodies, wounded bodies, and the specific image of “Americans killing Germans bodies.” However, even though there is change some things are turning into myths. The icon of the American soldier as a healthy and strong man willing to sacrifice his life for the country is still a major theme throughout all the exhibits. Finally, there are several myths that America has adopted from its allies. The icons of the bandages over the eyes from the chemical attacks and the horrors of the trenches are borrowed, to a certain extent, from America’s allies. The Americans were only in the war for a limited time and borrowed cultural memories to supplement their own. The examination of the four museums is important because this transition will happen again and soon. Museums must be conscious of the changes occurring during this transition in order to confront the challenges.
Keywords: World War I; History (0578)